A CROSS-SECTIONAL ANALYSIS OF INTENTIONALLY SELF-INFLICTED POISONING AMONG HOSPITALIZED PATIENTS. - Marndi, Chhatray; Behera, Ashok Kumar; Patra, Gopabandhu; Chhotaray, Saubhagya (Student's Journal of Health Research Africa, 2023)
Aim: This cross-sectional study aims to comprehensively investigate the prevalence, patterns, and underlying factors of deliberate self-poisoning among patients admitted to a tertiary healthcare center in India. The study contributes valuable insights into demographic characteristics, toxicological agents, and contextual factors influencing intentional self-poisoning in this specific healthcare setting. Methodology: The study employed a descriptive cross-sectional design, selecting 200 adult female participants from Bhima Bhoi Medical College and Hospital in India through purposive sampling. Inclusion criteria involved adult females with deliberate self-poisoning history, while ethical considerations were addressed with clearance from the hospital's Ethical Review Committee. Data analysis utilized SPSS, ensuring a meticulous and ethically sound investigation into deliberate self-poisoning among adult females. Results: The study, conducted in the Department of Medicine at Bhima Bhoi Medical College and Hospital in Balangir, Odisha, India, included 200 admitted female participants. Most participants were in the 21-29 age group (56%), with 69% below 30 years. Self-poisoning incidents were more common in rural areas and joint families. Insecticide was the predominant poison material, and family disharmony and romantic disappointment were the primary reasons for self-poisoning. Most participants recovered completely, with a higher fatality rate observed in rodenticide poisoning (66.6%). Conclusion: This study provides a comprehensive understanding of deliberate self-poisoning in a tertiary healthcare center in India, shedding light on demographic patterns, toxicological agents, and contextual factors. The findings underscore the need for targeted interventions to address the specific challenges posed by intentional self-poisoning in this healthcare setting. Recommendation: Implement targeted preventive strategies addressing demographic vulnerabilities, toxicological agent accessibility, and mental health awareness to reduce deliberate self-poisoning in Indian tertiary healthcare centers based on the findings of this cross-sectional study.